Living with Depression: Why Biology and Biography Matter Along the Path to Hope and Healing - Serani, Deborah (Rowman & Littlefield Publishers, 2023)
A comprehensive approach to living, and living WELL, with depression. One out of four Americans will experience mental illness in their lifetime; major depressive disorder is the leading cause of disability in the United States for ages 15 through 44. However, only a fraction of those suffering will seek treatment, leaving the rest alone to suffer in silence. In the fully updated second edition of Living with Depression, Serani outlines the various forms of depression, describes the different treatments, and outlines methods for living with depression and getting the help you or a loved one needs. However, since the first edition was published, much has changed in the landscape of depression including diagnostic aspects, new disorders, treatments and research, and Deborah Serani covers it all. Tips on how to choose a good therapist, negotiate the labyrinth of healthcare, and minimize stigma are addressed, as is learning how to use biology and biography as tools of empowerment. There is no other book that offers what “Living with Depression” – giving readers a dual perspective of what it’s like to know depression as a clinician and as a patient. As mental health issues are on the rise, finding resources to help sufferers and their loved ones do more than just cope is essential. Serani helps set readers on the path to living, and living well, with depression.